THE ROLE OF SOCIAL MEDIA MARKETING IN LOCAL GOVERNMENT INSTITUTION TO ENHANCE PUBLIC ATITUDE AND SATISFACTION - Miykel S. Poluan; Lefrand. S Pasuhuk; Deske W. Mandagi (Jurnal Ekonomi, 2022)
Social media marketing (SMM) is one of the fast-growing tools utilized by the government to disseminate information and communicate with the public in carrying out its function as a public service. Management of SMM in government institutions requires an organizational culture accompanied by support from all levels of government officials to share information with the public, encourage transparency, be open to improvement and increase collaboration with the public. This study aims to determine public perception of the influence and effectiveness of SMM as a communication tool in the context of South Minahasa Regency Government institutions. Descriptive quantitative research was designed to achieve this research objective and answer research questions. A quantitative survey utilizing the purposive sampling technique was conducted on 100 respondents who met the following criteria: (1) residents of the South Minahasa Regency (2) Actively use social media and have visited the official social media pages of the South Minahasa Regency Government (3) Willing to participate without reward. The structural equation modeling (SEM) was then performed utilizing SmartPLS statistical software. The result uncovers three important findings: 1) SMM has a significant and positive influence on the public’s attitudes 2) SMM has a significant and positive influence on public satisfaction; 3) Public attitude has a significant and positive influence on their satisfaction on governments’ institution.